2019
DOI: 10.1161/circep.118.006942
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Afferent Denervation Abolishes Ganglionated Plexi and Sympathetic Responses to Apnea

Abstract: Background: The autonomic nervous system response to apnea and its mechanistic connection to atrial fibrillation (AF) are unclear. We hypothesize that sensory neurons within the ganglionated plexi (GP) play a role. We aimed to delineate the autonomic response to apnea and to test the effects of ablation of cardiac sensory neurons with resiniferatoxin (RTX), a neurotoxic TRPV1 (transient receptor potential vanilloid 1) agonist. Methods Sixteen dogs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…OSA causes acute and long-time sympathetic autonomic nervous system activation by increasing pulmonary artery pressure and chemoreceptor activation caused by acidosis, hypoxia, and hypercapnia [ 17 ]. Previously, Tavares et al have shown that when blood SaO 2 levels decline, the sympathetic activation increases progressively [ 17 ]. Moreover, a cohort study showed that the lowest nocturnal O 2 saturation value and the mean O 2 saturation at night, are independent predictors of SCD [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…OSA causes acute and long-time sympathetic autonomic nervous system activation by increasing pulmonary artery pressure and chemoreceptor activation caused by acidosis, hypoxia, and hypercapnia [ 17 ]. Previously, Tavares et al have shown that when blood SaO 2 levels decline, the sympathetic activation increases progressively [ 17 ]. Moreover, a cohort study showed that the lowest nocturnal O 2 saturation value and the mean O 2 saturation at night, are independent predictors of SCD [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…58,59 Sympathetic denervation: stellate ganglion ablation In a recent study by Tavares et al, OSA increased vagal activation and caused tonic excitation of stellate ganglia, which correlated with a shortened effective refractory period and higher AF inducibility. 60 In patients with paroxysmal AF, unilateral ablation of the stellate ganglion reduced an incidence and duration of AF. 61…”
Section: Ablation Of Nerve Plexuses At the Openings Of Pulmonary Arterymentioning
confidence: 99%
“…Our group aimed to shed light on the autonomic response to apnoea and to test the effects of ablation of cardiac sensory neurons using the neurotoxic transient receptor potential vanilloid 1 (TRPV1) agonist resiniferatoxin (RTX) in an animal model. [ 28 ] Sixteen dogs were anaesthetised and ventilated with apnoea induced by stopping ventilation until oxygen saturations decreased to 80%. Nerve recordings from bilateral vagal nerves, left stellate ganglion and anterior right GP were obtained before and during apnoea.…”
Section: Neuromodulatory Approachesmentioning
confidence: 99%